Rancang Bangun Aplikasi Penjualan Berbasis Web Pada Percetakan Arbain Grafika Surabaya - Afifa, Anisa Noor; Ayuningtyas, Ayuningtyas; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Arbain Grafika Surabaya is an enterpreneurial business engaged in printing service. During the sales that have been conducted by Arbain Grafika Surabaya, there are some problems that occured, such as when the customers asked for a price of a product that they wished, they have to wait for a long time for the answer; the production division gets the information detail or work order letter behind the schedule from the owner because the owner forgets or giving the information unexpectedly, the administration division takes time to find the sales data in presenting the report desired by the owner, the administration division does not acknowledge the deadline of payment of customers that still have debts, the owner or administration is not able to acknowledge the customer’s product have been done or not and requires the information from the production division.  In order to solve those problems, it needs an aplication that helps the sales process. This application is based on the web that allows to calculate the product selling price, arranging customer’s orders and payments. The web-based selling application for Arbain Grafika Surabaya provides the reports that the owner needs. Furthermore, this web-based selling application also provides the information regarding the status of customers’ order, the status of customer’s payment, and work order letter.    Keywords: printing, sales, web based